Increasing resolution of airborne pollen forecasting at a discrete sampled area in the southwest Mediterranean Basin. (November 2019) - Picornell, A.; Oteros, J.; Trigo, M.M.; Gharbi, D.; Docampo Fernández, S.; Melgar Caballero, M.; Toro, F.J.; García-Sánchez, J.; Ruiz-Mata, R.; Cabezudo, B.; Recio, M.
Abstract: Daily fluctuations of the airborne pollen concentrations produce variations on symptomatology in allergic population. Such fluctuations are influenced by local vegetal coverage, flowering phenology, geography and climatology. Since 1991, airborne pollen of Malaga province (southern Spain) has been monitored in 7 different locations. Malaga station has been kept operational uninterruptedly throughout the studied period, while the rest of the stations only worked in periods of 2–4 years. Weekly, its pollen information is updated online to inform the population in order to prevent allergic diseases. Increasing the spatial resolution of pollen information would be very useful for allergic population living at unsampled locations. Due to the impossibility of keeping operational a high number of pollen stations covering the whole province of Malaga, the aim of this study is to create spatial models to extrapolate and forecast the pollen concentrations to Malaga province by using the concentrations registered at the capital as unique input. To do so, the relationships obtained between the airborne pollen concentrations detected at Malaga city and those detected at the other stations have been used to elaborate models for the main pollen types registered at the province. These models were spatially interpolated all over the province by using co-kriging techniques and the Compensated Thermicity Index as covariable. As result of this work, pollen distribution of the 8 most prevalent taxa has been depicted all over the whole Malaga province and an allergy alert system has been set up to extrapolate pollen information from Malaga to the whole province. Graphical abstract: Image 1 Highlights: Airborne pollen levels can be estimated at unsampled locations. Databases of sampling stations can be completed with data from neighbour stations. The Compensated Thermicity Index can be used to elaborate atmospheric pollen maps.